تحديد معامل التوصيل الهيدروليكي غير المشبع لتربة مختلفة في محتواها من المادة العضوية اعتماداً على الانتشارية الهيدروليكية - أسعد شذا أحمد (Latakia University Journal -Biological Sciences Series, 2016)
من خلال الدراسة التي أجريت على تربة طينية ثقيلة مختلفة في محتواها من المادة العضوية لتحديد الانتشارية الهيدروليكية ومعامل التوصيل الهيدروليكي غير المشبع بطريقة الهواء الساخن. أظهرت الدراسة ما يلي: - إن قيم الانتشارية الهيدروليكية ترواحت بين (0.23-0.12 )mm2/s ضمن مجال رطوبي 38-30% حجماً في تربة الشاهد, وتراوحت بين(0.73-0.22) mm2/s ضمن مجال رطوبي 41-31 %حجماً في التربة ذات المحتوى العضوي 1.78%, وبين (1.1-0.27) mm2/s في التربة ذات المحتوى العضوي 2.19% ضمن مجال رطوبي 43-32 %حجماً. وبالتالي فإن قيم الانتشارية تنخفض بشكل عام مع نقصان المحتوى الرطوبي لعينة التربة في حين أنها تزداد مع زيادة المحتوى العضوي لنفس عينة التربة . - تراوحت قيم معامل التوصيل الهيدروليكي غير المشبع بين (0.0001-0.024) م/يوم ضمن مجال شد رطوبي بين (4.2-1.8) في التربة ذات المحتوى العضوي 0.68%, أما في التربة ذات المحتوى العضوي 1.78% فلقد تراوحت القيم بين (0.00034– 0.04) م/يوم ضمن مجال شد رطوبي (4.2 – 2.2) م/يوم, بينما على التربة ذات المحتوى العضوي 2.19% تراوحت القيم بين (0.00093- 0.073) م / يوم ضمن مجال شد رطوبي (4.2- 2.35) وبالتالي فأنه بنقصان الرطوبة تنخفض قيمة معامل التوصيل الهيدروليكي غير المشبع. - قاربت قيمة معامل التوصيل غير المشبع من القيمة الحدية (0.0002) م/يوم عند محتوى رطوبي 33% وشد رطوبي 3.45 في التربة ذات المحتوى العضوي 0.68% أما بالنسبة للترب ذات المحتوى العضوي 1.78%, 2.19% لم تصل قيمة معامل التوصيل الهيدروليكي غير المشبع إلى القيمة الحدية حتى عند شد رطوبي 4.2. - المادة العضوية لعبت دوراً إيجابياً في تحسين المحتوى الرطوبي للتربة والماء المتاح وكان لها تأثير واضح في زيادة معامل التوصيل الهيدروليكي غير المشبع. Through the study, which was conducted on heavy clay soil in different content of organic matter to determine hydraulic diffusivity and hydraulic conductivity un saturated in a way the hot air .The study showed the following: - The hydraulic diffusivity values​ ranged between (0.23-0.12) mm2 / s with the field of moisture 38-30%by volume in the soil without organic matter, and ranged between(0.73-0.22) mm2 / s with the field of moisture 41-31% by volume in the soil which content 1.78% organic matter , while in the soil which content 2.19% organic matter the values has ranged between​​(1.1-0.27 ) mm2 / s with the field of moisture 43-32% by volume. so, the values ​​of diffusivity generally decrease when the moisture content of the soil sample decrease, while it increases when organic matter increases of the same soil sample. - the values of ​​ unsaturated hydraulic conductivity ranged between(0.0001-0.024) m /day with in the field of tension between the moisture(4.2 – 1.8) in the soil with 0.86% organic matter, while in the soil with 1.78% organic matter the values has ranged between ​​(0.00034- 0. 04)m /day with in the field of pulling moisture(4.2 to 2.2) m /day, while the soil with 2.19% organic content the values ranged between ​​(0.00093- 0.073) m /day with in the field of pulling moisture(4.2 to 2.35) .so that, the value of coefficient of the unsaturated hydraulic conductivity decreases when the value of moisture decreases. - The value of conductivity coefficient un saturated approached to the threshold value (0.0002) m/day by the pulling moisture of 3.45 and moister of 33% in the soil which content 0.68% organic matter, while for soils with 1.78%, 2.19% organic content did not reach the value of the coefficient of hydraulic conductivity un saturated to the threshold value even when pulling moisture 4.2. - The Organic matter play an important role in improve the soil moisture content, the percent of available water and its’ increase the unsaturated hydraulic conductivity coefficient .